Systemic Lupus Erythematosus Symptom Clusters and Their Association With Patient‐Reported Outcomes and Treatment: Analysis of Real‐World Data. Issue 7 (22nd April 2022) - Touma, Zahi; Hoskin, Ben; Atkinson, Christian; Bell, David; Massey, Olivia; Lofland, Jennifer H.; Berry, Pamela; Karyekar, Chetan S.; Costenbader, Karen H.
Abstract : Objective: To identify discrete clusters of systemic lupus erythematosus (SLE) patients based on symptoms and investigate differences across clusters. Methods: Data were collected in the US and 5 European countries via the Adelphi Real World Lupus Disease Specific Programme, a cross‐sectional survey. Rheumatologists provided data for 5 consecutively consulting adult patients with SLE, who were invited to participate. Identified SLE symptoms were reduced to factors based on commonly concurrent symptoms, using principal‐component factor analysis. Factors were used as covariates in a latent‐class cluster analysis to identify discrete patient clusters. Patient‐reported outcomes and physician‐reported data were compared across clusters. Results: Among 1, 376 patients, 87% were female and 74% were White. We identified 4 patient clusters (very mild, mild, moderate, and severe) based on 39 signs/symptoms. Physician‐reported symptom burden, organ involvement, disease activity, and the number of flares increased with increasing cluster severity ( P < 0.0001). Patient‐reported impact (health status, fatigue, work productivity impairment, anxiety/depression, and emotional impact) increased with increasing cluster severity ( P < 0.0001). Glucocorticoid and immunosuppressant use increased, and antimalarial use decreased, with increasing cluster severity. In all clusters, <20% of patients received biologics; >15% of patients not receiving biologics were considered eligible for treatment by their physician. The proportion of physicians and patients satisfied with treatment decreased with increasing cluster severity ( P < 0.0001). Conclusion: Our large, international, real‐world survey of SLE patients and physicians demonstrated strong associations between increased impairment, organ involvement, and humanistic burden in SLE, highlighting an unmet need for effective treatment options in patients with high disease activity.